The Significance of the Language Laboratory for Arabic Non-Native Speakers in the Arabic Teaching Institutes of Sri Lanka - Mohamed, Thalib (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
In Sri Lanka, where Arabic is not a native language, the Establishment of Arabic language laboratories presents significant opportunities for enhancing linguistical proficiency among non-native speakers.  This study aims to explore the impact of Arabic language laboratories on language proficiency and cultural understanding among non-native speakers in the Arabic teaching institutes of Sri Lanka and evaluate the effectiveness of technological tools in Arabic language laboratories for facilitating language acquisition among non-native speakers in the Arabic teaching institutes of Sri Lanka. This study concluded that Establishing Arabic language labs in the Arabic teaching institutes of Sri Lanka is a strategic investment, offering diverse benefits beyond linguistic proficiency. These labs foster cultural awareness and open avenues for academic and professional growth. Recommendations include investing in technology, updating the curriculum to reflect linguistic and cultural trends, and providing teacher training. Cultural immersion programs and ongoing research are also crucial. Collaboration with international partners and promoting Arabic learning are essential for enriching educational experiences and fostering a globally competitive workforce.